A case of lateral sinus insufficiency with acute otitis media: Early surgical intervention for prevention of lateral sinus thrombosis. Issue 6 (December 2015) - Takahashi, Kuniyuki; Yamamoto, Yutaka; Ogi, Manabu; Ohshima, Shinsuke; Morita, Yuka; Takahashi, Sugata
Abstract Objective To describe a case of lateral sinus insufficiency, presumably occurring just prior to lateral sinus thrombosis (LST), and to discuss the importance of early surgical intervention and the pathophysiology of full-blown LST. Case report A 4-year-old boy developed headaches and vomiting after exhibiting typical symptoms of acute otitis media. Contrast-enhanced CT revealed narrowing of the sigmoid sinus medially by gas and low-density material. We diagnosed the patient with suspected LST and consequently performed mastoidectomy. A large amount of bloody pus was found in the mastoid cavity and below the bony sinus plate. Sigmoid sinus blood flow was completely restored after drainage of the hemorrhagic and purulent material, and the patient recovered fully. Conclusion Because of the anatomical features of the dural venous sinus, hemorrhage per diapedesis may be strongly associated with the development of LST. In the patient with suspected LST, early diagnosis and surgery prior to the development of intravenous thrombus are key for full recovery from this condition.